Hydrogen as Fuel for ICEs: State of Art and Technological Challenges - Giovanni Cecere (Journal of Engineering)
The climate change, as the main consequence of the polluting emissions due to anthropic activities, is nowadays a well-known threat to human health as well as for the environment safety. Several plans and strategies have been announced by the governments to detach from fossil fuel-based energy and gradually reduce the carbon footprint of their economies. In this scenario, the road transport sector is turning out to be the main “technological gym” to test and improve new powertrain solutions to achieve as soon as possible the goal of the net-zero carbon emissions, at least in the tank-to-wheel (TTW) context. In view of this, the hydrogen as fuel is gaining ever more attention from the scientific community, both as the middle-term solution to achieve the abovementioned goal and as a prominent future energy carrier. In this review, the performance and main characteristics of the hydrogen-internal combustion engines (H2-ICEs) are discussed based on the most recent studies available in literature. A comprehensive overview of various topics is offered, from the production stage to the combustion anomalies, mixture formation strategies, and the challenge of reducing the nitrogen oxides (NOx) emissions under high load conditions.